Seeking for Recovering Their Identity: The Melanesian-Papua Treading Returning Roadmap - Don Augusthinus Lamaech Flassy (Journal of Social and Development Sciences, 2017)
The study describes 5 main areas, namely, (1)"Hidden Structure" that in the Social Meaning of Melanesian-Papua Cultural highlights Papuanistiecs and Melanesianology; (2) The Prestige and Power exposes the influence of the Big World Power to the problem of Papua; (3) Federalism in Indonesia reveal to the Melanesian-Papua in Land Papua as Special Specific Case versus unitary of The Republic of Indonesia; (4) Constitution vis-Ã -vis Constitution on constitutional philosophical correlation Indonesia constitution 1945 versus Papua constitution 1999; (5) Unilateral Declaration of Independence/UDI October 19, 2011, concerning Freedom-Melanesian Papuans in Land Papua as Nation and State. The background of this study is based on two main thoughts keys, namely: First, Meteray (2012: 268, 2013: 4) confirmed that, during the 17 years from 1945 to 1962, the process to Indonesian-sizing the Papuans are generally still in the stage of seeding while growth only in some areas of government and urban centresâ€™. Awareness to be Indonesian-ness is yet to reach all areas of Papua. Meteray adding that the presence of Indonesian-sizing in past greatly influenced by the policies and the approach taken by both the Dutch and Indonesian government through the role of nationalists initiators of the period (2012: 264-267); Second; LIPI study in 2007 (Soewarsono, ed) are still questions to the Indonesian-sizing of the Papuans reinforce the view of Meteray stated that it is to Indonesian-sizing among the Papuans still weak (Meteray 2013: 1). Meteray concluded that, in fact, to understand the history of Papua will become a basic reference for the government seek and find out the right way and dignified in overcoming the issues of Papua, though on the other hand Aditjondro, 1999 clamming, the Government and Important People of Indonesia has curled the history of Papua which by the Papuans wanting to be straightened out, He calls this act as: "The dark history of Papua in Indonesian Historiography". Thoughts of Meteray and Aditjondro strengthens the authors thought that the various problems occurred in Papua, especially the facts involves "M"/Merdeka (Freedom) Papua". Referring to the failure of Indonesian-sizing of the Papuans, it appears that it is not necessary regrettable because in fact, they are different. Precisely when indecision of the President of Indonesia to the case of Papua is safe step into alternative measures of the Melanesian-Papua people themselves must be hacked through, UDI October 19, 2011. This research focuses on the study of literature and interviews with the method of Descriptive Analysis and Method of Structure Linkage to assemble the Hidden Structure and Correlation Studies to reflect the relationships between aspects on the basis of Motivation Theory, Theory of Social Change and Theory of Balance and Theory of Realist and related by make use of Hidden Structure as Grand Theory. The formulation of the problem is (1). How to understand the present of Melanesian-Papuans in Land Papua? (2). Whether existing of Papua as "trust territory" of the UN is still attracting the winning of Prestige and Power of "the Big Power of the World" to be back to discusses at the UN of a future in accordance with Article 74 and Article 78 of the UN Charter? (3). Whether, Melanesia-Papua and Indonesian in Papua can together according to the federalist order of Melanesian-Papua? (4). How is the condition of social customs and traditions of Indonesia and Papua can be met?